2019
DOI: 10.2139/ssrn.3438270
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Filtering: The Strategic Use of Electoral Fraud in Russia

Abstract: Incumbents have many tools to tip elections in their favor, yet we know little about how they choose between strategies. By comparing various tactics, this paper argues that electoral malpractice centered on manipulating institutions offers the greatest effectiveness while shielding incumbents from public anger and criminal prosecution. To demonstrate this, I focus on one widespread institutional tactic: preventing candidates from accessing the ballot. First, in survey experiments, Russian voters respond less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, these traits don’t appear to mediate the treatment effect, nor do they help to explain why the bought votes treatment leads to a less negative response. In Section C4 of the supplementary material, we discuss possible explanations for these null findings and reiterate the call for more research on why some individuals approve or disapprove of certain electoral manipulations (Szakonyi forthcoming).…”
mentioning
confidence: 82%
“…In addition, these traits don’t appear to mediate the treatment effect, nor do they help to explain why the bought votes treatment leads to a less negative response. In Section C4 of the supplementary material, we discuss possible explanations for these null findings and reiterate the call for more research on why some individuals approve or disapprove of certain electoral manipulations (Szakonyi forthcoming).…”
mentioning
confidence: 82%
“…Moscow along with St. Petersburg are the cities with the highest number of independent election observers that limit opportunities for outright fraud, and their importance has increased during the last decade. The evidence is also accumulating that incumbents in Russia often revert to electoral manipulation strategies that are less visible than ballot-box stuffing and less costly in terms of public attention and fury: they manipulate institutions and electoral rules to prevent challengers from running in the first place (Szakonyi 2019). Indeed, the independent watchdog "Golos" agreed that Moscow 2018 elections did not experience fraud, though it questioned the fairness of the incumbent's electoral strategies (https://www.kommersant.ru/doc/3737769, [last accessed September 2020]).…”
Section: Appendix Tablementioning
confidence: 99%
“…For instance, regarding the relationship between overt electoral fraud and electoral systems, Birch (2007) and Fjelde and Hoglund (2016) have found that majoritarian electoral systems are more likely to be accompanied by higher levels of electoral cheating and electoral violence. Using a dataset of municipal elections in Russia, Szakonyi (2019) argues that deregistration of opposition candidates is a substitute for more blatant forms of electoral fraud, such as ballot stuffing. By engaging with these emerging studies on the selection of electioneering techniques, this book focuses on the relationship between two broad categories of electioneering strategy: electoral manipulation (i.e., blatant electoral fraud and institutional manipulation) and pre-electoral economic maneuvering.…”
Section: The Menu Of Electoral Manipulationmentioning
confidence: 99%